The tempo and mode of angiosperm mitochondrial genome divergence inferred from intraspecific variation in Arabidopsis thaliana - Wu, Zhiqiang, author; Waneka, Gus, author; Sloan, Daniel B., author; Genetics Society of America, publisher (Colorado State University. Libraries, 2020)
The mechanisms of sequence divergence in angiosperm mitochondrial genomes have long been enigmatic. In particular, it is difficult to reconcile the rapid divergence of intergenic regions that can make non-coding sequences almost unrecognizable even among close relatives with the unusually high levels of sequence conservation found in genic regions. It has been hypothesized that different mutation/repair mechanisms act on genic and intergenic sequences or alternatively that mutational input is relatively constant but that selection has strikingly different effects on these respective regions. To test these alternative possibilities, we analyzed mtDNA divergence within Arabidopsis thaliana, including variants from the 1001 Genomes Project and changes accrued in published mutation accumulation (MA) lines. We found that base-substitution frequencies are relatively similar for intergenic regions and synonymous sites in coding regions, whereas indel and nonsynonymous substitutions rates are greatly depressed in coding regions, supporting a conventional model in which mutation/repair mechanisms are consistent throughout the genome but differentially filtered by selection. Most types of sequence and structural changes were undetectable in 10-generation MA lines, but we found significant shifts in relative copy number across mtDNA regions for lines grown under stressed vs. benign conditions. We confirmed quantitative variation in copy number across the A. thaliana mitogenome using both whole-genome sequencing and droplet digital PCR, further undermining the classic but oversimplified model of a circular angiosperm mtDNA structure. Our results suggest that copy number variation is one of the most fluid features of angiosperm mitochondrial genomes.
Arabidopsis mitogenome variation
January 21, 2020.
Keywords: copy number variation; mutation accumulation line; mutation rate; recombination; single nucleotide polymorphisms